Soft Fixed Point Theorems for the Soft Comparable Contractions - Chi-Ming Chen; Zhi-Hao Xu; Erdal Karapinar (Journal of Function Spaces)
In this article, we introduce the notions of a soft inf-comparable contraction and soft comparable Meir-Keeler contraction in a soft metric space. Furthermore, we prove two soft fixed point theorems which assure the existence of soft fixed points for these two types of comparable contractions. The obtained results not only generalize but also unify many recent fixed point results in the literature.